Complicaciones obstétricas en adolescentes en el primer y segundo trimestre del embarazo atendidas en el Área de Salud N° 3. - Cabrera Beltrán, Juleisy Mireya (2016)
This research work was retrospective, descriptive and correlate study type of all medical records of pregnant teenagers who were treated at the Health area Nº 3 of the city of Loja, during the period from June to September 2016. The population was of 200 pregnant teenagers, being the sample of 55 pregnant teenagers between 10 and 19 years old who met the inclusion criteria. It was aimed to identify obstetric complications in teenagers in the first and second pregnancy periods, specifically to determine the age of the group, education level and compare the complications of the first with second period of the pregnant teenagers. Through this study the following results were obtained: The most frequent complications during the first period was urinary tract infection with 32% and iron deficiency anemia with 28% in the second period the most frequent complications was vaginitis with 30% and urinary tract infection with 26.7%, the teenagers between 15 and 19 years with a 87.28% were the most affected population, concluding that the main complications for both the first and the second pregnancy periods are the urinary tract infection and vaginitis, in this groups of teenagers. Keywords: Pregnancy, teenagers, obstetric complications.